FBI : Reckoning - Book 26 - Coulter, Catherine (New York, NY : William Morrow, 2022)
"Agents Savich and Sherlock are back in the latest installment in Catherine Coulter's #1 New York Times bestselling FBI Thriller series, and this time both are enlisted to help women with traumatic pasts who are in mortal danger"--
Keywords: Suspense